Combining Experimental and Computational Tools to Unravel Copper-Based Metallodrug Interactions With Proteins - Quim Peña; Iker Zapirain-Gysling; A. Jalila Simaan; Mercè Capdevila; Olga Iranzo; Òscar Palacios; Jean-Didier Maréchal; Pau Bayón (Bioinorganic Chemistry and Applications)
Metallodrugs are widely used in the treatment of several diseases, including cancer. Many bloodstream proteins exhibit high affinities for metals and metal-based compounds, and these interactions have been shown to impact metallodrug pharmacokinetics and pharmacodynamics, ultimately influencing their therapeutic performance. Several spectroscopic, spectrometric, and computational techniques have been used to further understand drug–protein binding modes at the molecular level over the last few years. However, there is still plenty of room to ascertain the full potential of integrated experimental–computational methodologies in the field of metallodrugs. These studies have mostly been limited to a few metal-containing systems, such as platinates and vanadium drugs. In this work, we aim to expand and validate the use of combined experimental–theoretical approaches in studying copper (Cu)-based drug interactions with proteins. To do so, a tetracoordinated Cu(II) complex has been employed as a practical case study, and its interactions with several relevant proteins using different experimental and computational techniques have been evaluated, including electron paramagnetic resonance spectroscopy, mass spectrometry, density functional theory, and protein–ligand docking calculations. Experimental data highlight interactions of the Cu(II) complex with albumin, myoglobin, and cytochrome C. Further insights into the preferential modes of binding were evaluated by density functional theory and docking calculations, which revealed three main outer surface binding sites for both albumin and myoglobin, as well as three preferential inner pockets in the case of albumin. The most relevant binding modes found for both proteins include noncoordinative interactions with the Cu(II) dimeric structure intact upon binding, as well as metal–ligand exchange and direct metal–amino acid coordination, mainly to glutamate/aspartate residues after cleavage of the dimer. Altogether, an example of the applicability of a mixed experimental–theoretical framework in the study of Cu-based drug interactions with relevant proteins is shown.